The application of nanofibrous membranes with antimicrobial agents as filters - Gregg, Andrea (Kansas State University, 2010)
Nanofibers are classified as fibers less than 1 micrometer in diameter. These fibers can be layered to form nanofibrous membranes, and these membranes offer great potential in the filtration industry. The membranes' smaller fiber diameters and pore sizes permit such filters to filter out more and smaller particulate. Additionally, antimicrobial agents can be incorporated into the membrane to inhibit fungal and bacterial growth on the membrane’s surface. This report evaluates nanofibrous membranes with antimicrobial agents and their potential in two specific locations: cleanrooms and protective environment rooms, where bacterial and fungal growth would have a detrimental effect on the process or occupant of the space.
Keywords: Nanofibrous membranes; Nanofiber; Antimicrobial agents; Filtration; Air; High efficiency; Engineering, Mechanical (0548)